The effect of Material used in the Lime Infused water Packaging on Vitamin C Level: Pengaruh Bahan Kemasan Penyimpanan Minuman Infused Water Jeruk Nipis terhadap kadar Vitamin C - Vika Ayu Devianti; Djamilah Arifiyana (Akademi Farmasi Surabaya, 2022)
The storage process can affect the level of vitamin C in lime Infused water. The purposes of this research was to know the effect of storage container on vitamin C level in lime Infused water. The material used in the Infused water packaging are plastic and glass. Analysis of vitamin C levels in sample using Iodimetric method. The results of this research indicated that vitamin C levels in plastic and glass container was 2,499 mg/100 mL and 3,034 mg/100 mL, respectively. The siginificants results (Sig 2-tailed) of this study was 0,235 (p<0,05). From this study can be concluded that the use of plastic and glass packaging affect the vitamin C level in lime Infused water.